Antithrombotic Therapy in Acute Coronary Syndromes: Current Evidence and Ongoing Issues Regarding Early and Late Management - Guedeney, Paul; Collet, Jean-Philippe (Thrombosis and Haemostasis, 2021)
A few decades ago, the understanding of the pathophysiological processes involved in the coronary artery thrombus formation has placed anticoagulant and antiplatelet agents at the core of the management of acute coronary syndrome (ACS). Increasingly potent antithrombotic agents have since been evaluated, in various association, timing, or dosage, in numerous randomized controlled trials to interrupt the initial thrombus formation, prevent ischemic complications, and ultimately improve survival. Primary percutaneous coronary intervention, initial parenteral anticoagulation, and dual antiplatelet therapy with potent P2Y12 inhibitors have become the hallmark of ACS management revolutionizing its prognosis. Despite these many improvements, much more remains to be done to optimize the onset of action of the various antithrombotic therapies, for further treating and preventing thrombotic events without exposing the patients to an unbearable hemorrhagic risk. The availability of various potent P2Y12 inhibitors has opened the door for individualized therapeutic strategies based on the clinical setting as well as the ischemic and bleeding risk of the patients, while the added value of aspirin has been recently challenged. The strategy of dual-pathway inhibition with P2Y12 inhibitors and low-dose non-vitamin K antagonist oral anticoagulant has brought promising results for the early and late management of patients presenting with ACS with and without indication for oral anticoagulation. In this updated review, we aimed at describing the evidence supporting the current gold standard of antithrombotic management of ACS. More importantly, we provide an overview of some of the ongoing issues and promising therapeutic strategies of this ever-evolving topic.
Keywords: antiplatelet agents; acute myocardial infarction; coronary syndrome